Investigating the information gaps in refugee integration. Issue 1 (24th October 2017) - Oduntan, Olubukola; Ruthven, Ian
ABSTRACT: Refugee integration processes and systems are complex for refugees. They find them difficult to navigate and thus often end up disadvantaged. This paper presents the first set of findings from an ongoing information behaviour research study into refugee integration. The study explores the situational experiences of refugees and asylum seekers engaging with integration processes and systems through individual semi‐structured interviews. Dervin's sense‐making methodology was used to elicit the information gaps. The findings reveals refused asylum situation during integration and highlight information needs embedded in processes and systems of refugee integration. The results have implications for reducing the complexity of service provision during refugee integration. In addition, the approach expands previous studies and highlights the depth a situational investigation can bring to information behaviour studies.